Prolegomena to a Future Legal Methodology and to a Non-Sacred Legal Theory - Ivanov, Viktor (Research Papers, 2018)
The title of the study is a paraphrase of Kant’s work „Prolegomena to any Future Metaphysics (Prolegomena zu einer jeden kunftigen Metaphysik)“The study sets out and defends the understanding that only the Legal Methodology derived from the integral development of scientific knowledge and which is based on the general methodology of science as a subject of management of the system-based scientific knowledge manifesting itself in its static, as well as in its dynamic form, as a continuous process of growth of the conceptual apparatus of science and the multiplication and deepening of scientific hypotheses and theories, and only such a legal methodology will meet the high modern requirements for a scientific methodology.On the other hand, the formation of a modern legal methodology, which is a product of the New Age Cultural Paradigm (NACP), will inevitably lead to reformatting of legal theory and to the construction of a new Non-sacred legal theory (and theory of the state).The Non-sacred legal theory must have the following characteristics: to be critically rational, anti-dogmatic, anti-apologetic, synthetically-encyclopedic, non-sacred (non-bewitched, disenchantment, non-fetishizing, Entzauberung) and paradoxical in its logical structure, but aiming for exquisitely non-contradictory presentation and expression.For the creation of such a legal theory, the author relies upon the drawn up by the author basic law of the KPNV - the Law for the Expanded Reproduction of the Theoretical Knowledge (Law for Extended Reproduction of Critical-Rational Notion Systems, which reveals the processes of reproduction of scientific knowledge, processes which in their essence are non-sacred (anti-fetishizing, non-bewitched) processes of rational and critical understanding of reality.